The Relationship Between Revascularization Extent and the Long‐term Prognosis of Patients With Stable Angina Pectoris and Three‐Vessel Disease Treated by Percutaneous Coronary Intervention in the Era of Drug‐Eluting Stents. Issue 9 (14th August 2014) - Li, Quan; Yu, Xianpeng; He, Jiqiang; Gao, Yuechun; Zhang, Xiaoling; Wu, Changyan; Luo, Yawei; Zhang, Yuchen; Ren, Xuejun; Lv, Shuzheng; Chen, Fang
ABSTRACT Background The effects of revascularization extent (RE) on the long‐term prognosis of patients with stable angina pectoris and 3‐vessel disease who underwent percutaneous coronary intervention were unknown. Hypothesis The study was aimed at evaluating whether there was an effect of RE on patients presenting with stable angina pectoris and 3‐vessel disease. Methods RE, which was calculated by baseline SYNTAX (Synergy Between Percutaneous Coronary Intervention With Taxus and Cardiac Surgery) score minus residue SYNTAX score divided by baseline SYNTAX score, was initially used in our study. Five hundred fifty‐eight patients presenting with stable angina pectoris and 3‐vessel disease were assigned to and compared among tertiles according to RE and clinical outcomes. The primary end point was the major adverse cardiovascular event (MACE), a composite of cardiac death, nonfatal myocardial infarction (MI), and any repeat revascularization. Results The median follow‐up period was 56.9 months (interquartile range, 52.1–63.6). The incidence of MACE increased significantly as RE increased (13.3%, 31.4%, and 44.1%, log‐rank P < 0.001). The same tendency was observed in occurrences of target‐vessel failure (TVF) (a composite of cardiac death, MI, or target‐vessel revascularization) (8.8%, 20.3%, and 28.4%, log‐rank P < 0.001), repeat revascularization (11.8%, 26.2%, and 35.6%, log‐rank P < 0.001), and MI (1.1%, 2.9%, and 12.6%, log‐rank P < 0.001). Multivariate analysis confirmed the tendencies mentioned above. Conclusions For patients presenting with stable angina pectoris and 3‐vessel disease, the increasing extent of revascularization resulted in a less favorable prognosis.